2006
DOI: 10.1159/000094146
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Potentiates Endotoxin-Induced Allopregnanolone Concentrations in the Newborn Brain

Abstract: Background: Allopregnanolone is a neurosteroid produced in the brain that can alter the excitability of the CNS. Neurosteroids have neuroprotective properties, and their elevation in response to stress may protect the newborn brain following infection or hypoxia. Infection, particularly of the respiratory tract, may lead to episodes of hypoxia. Infection and hypoxia have been identified as factors contributing to neonatal morbidity and mortality. Objectives: To determine the effect of acute episodes of hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 68 publications
3
3
0
Order By: Relevance
“…This could be explained if growth restriction in utero had impaired the development of neurosteroidogenic capacity in some tissues; for example, a reduction in the capacity of the adrenal gland to contribute to plasma, and therefore to brain allopregnanolone levels. In newborn lambs, we have shown that the adrenal glands make a major contribution to circulating allopregnanolone concentrations [15]. These findings are consistent with the concept that immediately after birth, the neonate experiences a transitional period during which steroidogenic capacity is low, and the brain loses the protective effect of these GABA A receptor-modulating substances.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This could be explained if growth restriction in utero had impaired the development of neurosteroidogenic capacity in some tissues; for example, a reduction in the capacity of the adrenal gland to contribute to plasma, and therefore to brain allopregnanolone levels. In newborn lambs, we have shown that the adrenal glands make a major contribution to circulating allopregnanolone concentrations [15]. These findings are consistent with the concept that immediately after birth, the neonate experiences a transitional period during which steroidogenic capacity is low, and the brain loses the protective effect of these GABA A receptor-modulating substances.…”
Section: Discussionsupporting
confidence: 82%
“…Evidence suggests that neurosteroid content in the fetal brain is not significantly determined by adrenal steroidogenesis or hypothalamic-pituitary activity [11,12,13]. Thus, an effect of uteroplacental insufficiency may be to reduce the availability of precursors for the synthesis of allopregnanolone by the fetal brain, even though the prevailing chronic hypoxia is likely to induce increased expression of key enzymes, such as P450scc and 5αRII [14, 15], and thus increase brain allopregnanolone production. In pregnant sheep, partial embolization of the placenta resulted in elevated expression of 5-reductase enzymes in the fetal brain without a concomitant increase in brain allopregnanolone concentrations [2].…”
Section: Introductionmentioning
confidence: 99%
“…The brain allopregnanolone concentrations were also increased following exposure to hypoxia in these newborn animals, but without a change in plasma concentrations [55], further supporting our contention that allopregnanolone production in the brain is regulated independently of peripheral sources after birth. Importantly, we found that when episodes of hypoxia were combined with LPS treatment, there was a greater increase in brain allopregnanolone concentrations in the majority of the brain regions examined as compared with either of the treatments alone [55].…”
Section: Neurosteroid Responses To Stress In the Newbornsupporting
confidence: 70%
“…Importantly, we found that when episodes of hypoxia were combined with LPS treatment, there was a greater increase in brain allopregnanolone concentrations in the majority of the brain regions examined as compared with either of the treatments alone [55]. Furthermore, areas that were largely unaffected by the individual challenges of LPS treatment or hypoxia, such as thalamus/hypothalamus and cerebellum, showed a marked increase in allopregnanolone concentrations, when lambs received LPS treatment together with exposure to hypoxia.…”
Section: Neurosteroid Responses To Stress In the Newbornmentioning
confidence: 99%
“…There is also some evidence of secondary effects that can suppress neural function, such as upregulation of intracerebral levels of the inhibitory neuromodulator allopregnanolone after i.v. LPS in newborn lambs, from 2-6 h [38] . Induction of neuroactive steroids by LPS may help inhibit cerebral and systemic TNF production [39] , and may be neuroprotective [40] .…”
Section: Discussionmentioning
confidence: 99%